Improved production technology of sunnhemp - Tripathy, M K; Mitra, Sabyasachi; Sarkar, S K; Sinha, M K; Mahapatra, B S (Indian Farming, 2015)
The crop grows best in tropical and subtropical climates within a temperature of 23-24Â°C and rainfall variation of 40-50 cm. In northern India, second fortnight of April is the best for sowing sunnhemp under irrigated condition while under rainfed condition the crop is sown with the onset of monsoon. Application of organic manure @ 2-3 tonnes/ha during land preparation along with 20 kg N/ha, 20-40 kg P2O5 and 20-40 k2O/ha sowing improves nodulation and increases fibre yield of sunnhemp. Sowing in April requires about 4-5 irrigations at 15-26 day interval. The fibre yield of sunnhemp under improved package of practices is 10-12 q/ha.